Purification and preliminary crystallization of alanine racemase from Streptococcus pneumoniae - Strych, Ulrich (BioMed Central, 2007)
BACKGROUND: Over the past fifteen years, antibiotic resistance in the Gram-positive opportunistic human pathogen Streptococcus pneumoniae has significantly increased. Clinical isolates from patients with community-acquired pneumonia or otitis media often display resistance to two or more antibiotics. Given the need for new therapeutics, we intend to investigate enzymes of cell wall biosynthesis as novel drug targets. Alanine racemase, a ubiquitous enzyme among bacteria and absent in humans, provides the essential cell wall precursor, D-alanine, which forms part of the tetrapeptide crosslinking the peptidoglycan layer. RESULTS: The alanine racemases gene from S. pneumoniae (alr(SP)) was amplified by PCR and cloned and expressed in Escherichia coli. The 367 amino acid, 39854 Da dimeric enzyme was purified to electrophoretic homogeneity and preliminary crystals were obtained. Racemic activity was demonstrated through complementation of an alr auxotroph of E. coli growing on L-alanine. In an alanine racemases photometric assay, specific activities of 87.0 and 84.8 U mg(-1 )were determined for the conversion of D- to L-alanine and L- to D-alanine, respectively. CONCLUSION: We have isolated and characterized the alanine racemase gene from the opportunistic human pathogen S. pneumoniae. The enzyme shows sufficient homology with other alanine racemases to allow its integration into our ongoing structure-based drug design project.